Septic Bursitis in an 8-Year-Old Boy - Panagiotis Kratimenos; Ioannis Koutroulis; Dante Marconi; Jennifer Ding; Christos Plakas; Margaret Fisher (Case Reports in Pediatrics)
Background. The prepatellar bursa can become inflamed owing to repeated trauma. Prepatellar bursitis is extremely rare in children. Methods. We report the case of an 8-year-old boy who was treated for an erythematous, swollen, and severely painful right knee, fever, inability to bear weight on the leg, and purulent material draining from a puncture wound. We describe the differential diagnosis for tender swollen knee, including infection, gout, rheumatoid arthritis, and osteoarthritis. If untreated, prepatellar bursitis can progress to patellar osteomyelitis. Results. Wound cultures grew Streptococcus pyogenes, with the infection resolving with amoxicillin. Conclusions. A high index of suspicion is necessary in children presenting with prepatellar bursitis to prevent potentially devastating sequelae of infection of the septic joint.